The Effect of Micro Radiation on Microbial DNA - Nurul Pratiwi; Cindy Pramila; Fira Safitri; Syifa Kamila Namidya; Dwi Hilda Putri (Jurnal Serambi Biologi, 2023)
Aim One of the important steps in molecular studies is DNA extraction. Many methods have been developed for bacterial DNA extraction, using either kits or boiling techniques. For the boiling technique, heating can be done using a water bath, heatblock, and microwave. Microwave is a tool that uses micro radiation rays. This study aims to determine the effect of microwave irradiation on bacterial DNA. Methods The isolates used in this study were B.J.T.A.2.1 isolates which were inoculated into NB medium. Microwave exposure was carried out for 0, 30, and 90 seconds. Cultures were isolated using the QIAamp DNA Mini Kit. The quality of DNA after exposure to the microwave was analyzed from the electrophoretic DNA bands of PCR RAPD products. Results Microwave exposure of bacteria causes changes to DNA. PCR RAPD reaction using isolated DNA from bacteria exposed to microwaves produces new bands on electrophoresis results. The longer the bacteria are exposed to the microwave, the brighter and thicker the new DNA banding pattern will be. Main conclusion Microwave exposure to bacterial culture affects the isolated DNA. The longer the culture is exposed to the microwave, the brighter and thicker the new DNA banding pattern will be.